2007
DOI: 10.1677/joe-07-0064
|View full text |Cite
|
Sign up to set email alerts
|

Obesity increases free thyroxine proportionally to nonesterified fatty acid concentrations in adult neutered female cats

Abstract: The obese cat is a model for the study of the progression toward type 2 diabetes. In this study, the impact of obesity on the hypothalamic-pituitary-thyroid axis was examined in 21 domestic shorthair cats before and after the development of obesity, which significantly increased body mass index (BMI), % body fat (BF), and girth (P!0 . 0001 for all). Serum total thyroxine (TT 4 ), tri-iodothyronine, free T 4 (FT 4 ) by direct dialysis, nonesterified fatty acids (NEFA), and leptin were measured, and FT 4 fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…No increase in thyroid-stimulating hormone was found with weight gain in cats, although free T4 was increased with obesity, likely because of increased NEFA concentrations. 70 In obese dogs, total T4 and triiodothyronine were both slightly increased, but there was no change in thyroid-stimulating hormone or free T4. 71 Insulinlike growth factor-1 concentrations have also been reported to increase with development of obesity in dogs.…”
Section: Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 90%
“…No increase in thyroid-stimulating hormone was found with weight gain in cats, although free T4 was increased with obesity, likely because of increased NEFA concentrations. 70 In obese dogs, total T4 and triiodothyronine were both slightly increased, but there was no change in thyroid-stimulating hormone or free T4. 71 Insulinlike growth factor-1 concentrations have also been reported to increase with development of obesity in dogs.…”
Section: Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 90%
“…The higher fasting NEFA concentrations in obese cats were likely caused by lower lipoprotein lipase activity (24) and may have led to the trend toward an increase in FT4 concentration because we have previously shown that the in vitro addition of palmitate and oleate to cat plasma, within a physiological concentration range, leads to a significant increase of the free T4 fraction (17).…”
Section: Discussionmentioning
confidence: 99%
“…At time 0, a bolus of 50% dextrose (0.5 g/kg; Hospira, Lake Forest, IL, USA) was injected intravenously. Blood samples were collected at 2, 3,4,5,6,8,10,12,14,16,19,22,24,25,27,30,40, 50, 60, 70, 80, 90, 100, 120, 140, 160, and 180 min. At 20 min after glucose injection, regular human insulin (Humulin R; Lilly, Indianapolis, IN, USA; 0.05 U/kg) was injected via the central catheter.…”
Section: Insulin Sensitivity Testingmentioning
confidence: 99%
“…As fat concentrations rise, leptin is released from adipocytes and targets areas of the brain such as the hypothalamus to reduce food intake and increase energy expenditure [2]. Leptin correlates positively with body fat mass in cats [3][4][5][6][7] and appears to correlate positively with insulin resistance, independent of adiposity [8].…”
Section: Introductionmentioning
confidence: 99%